Parental burnout and sexual dysfunction among postpartum women - Nurvitasari, Rifzi Devi; Lestari, Dwi Indah; Wieminaty, Aldi Febrian (JOURNAL OF Mental Health Concerns, 2026)
Background: Postpartum care frequently prioritizes physical recovery while overlooking the psychological determinants of reproductive health. Purpose: To analysed the relationship between parental burnout and sexual dysfunction among postpartum women. Method: A quantitative cross-sectional study was conducted with 144 postpartum mothers at Community Health Center Ardimulyo using purposive sampling. Participants completed the Parental Burnout Assessment (PBA) and Female Sexual Function Index (FSFI). Data were analysed using Spearman’s Rho and Multiple Logistic Regression (p<0.05). Results: Prevalence of moderate-to-high parental burnout was 38.2%, with 54.2% of respondents at risk for sexual dysfunction. A significant negative correlation was identified (